Characteristics of sheltered homeless families. - Bassuk, E L (1986)
To describe the characteristics of homeless families, we interviewed 80 homeless mothers and 151 children living in 14 family shelters in Massachusetts (two-thirds of the shelters in the state). Ninety-four per cent of the families were headed by women, 91 per cent were on AFDC (aid to families with dependent children), with twice as many as the state average having been on AFDC for at least two years; most had long histories of residential instability. Although 60 per cent had completed high school, only a third had worked for longer than one month. One-third of the mothers reported having been abused during their childhood, and two-thirds had experienced a major family disruption. At the time of the interview, almost two-thirds either lacked or had minimal supportive relationships and one-fourth of these named their child as the major support. Eighteen mothers were involved with the Department of Social Services because of probable child abuse or neglect. Seventy-one per cent of the mothers had personality disorders. In contrast to many adult homeless individuals, however, deinstitutionalized persons or those suffering from psychoses were not overrepresented. About 50 percent of the homeless children were found to have developmental lags, anxiety, depression, and learning difficulties, and about half required further psychiatric evaluation. Two-thirds described housing and social welfare agencies as not helpful. Given the many serious problems of the mothers and the difficulties already manifested by their children, comprehensive psychosocial and economic interventions must be made to interrupt a cycle of extreme instability and family breakdown.